Plausible Protective Role of Encephalartos villosus Extract in Acetic-Acid-Induced Ulcerative Colitis in Rats - Ashwag S. Alanazi; Mohammed M. Alanazi; Engy Elekhnawy; Nashwah G. M. Attallah; Walaa A. Negm; Aya H. El-Kadem (Pharmaceuticals, 2023)
Ulcerative colitis (UC) is an inflammatory ailment of the intestine associated with the upregulation of oxidative stress and pro-inflammatory cytokines. Here, we aimed to assess the consequences of Encephalartos villosus (EV) Lem extract on acetic acid (AA)-induced UC. Rats were randomly classified into five groups, as follows: control, AA, AA + mesalazine, AA + EV (50 mg/kg), and AA + EV (100 mg/kg) groups. EV (50 mg/kg and 100 mg/kg) and mesalzine (100 mg/kg) were administered orally for 14 days before the induction of UC. On the last day of the experiment, colitis was provoked via the intra-rectal delivery of 3% AA. Then, after 24 h, the rats were sacrificed and their colon tissues were isolated and inspected. Interestingly, EV pretreatment substantially (p < 0.05) reduced the elevated colon weight/length ratio and ulcer area and normalized the histological changes and immunohistochemical features. In addition, EV efficiently reduced the levels of myeloperoxidase (MPO) and increased the activity of glutathione peroxidase (GS-PX) and catalase (CAT). EV (100 mg/kg) resulted in a downregulation of toll-like receptor 4 (TLR-4) and upregulation of heme oxygenase 1 (HO-1) and occludin expression levels. Concerning the anti-inflammatory mechanisms, EV reduced the levels of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and nuclear transcription factor kappa B (NF-ĸB) and inhibited cyclooxygenase-2 (COX-2) expression levels. It also decreased caspase-3 levels. Our results indicate that the oral intake of EV improves AA-induced colitis in rats through its antioxidative effects and the modulation of pro-inflammatory cytokines, as well as the restoration of mucosal integrity. Consequently, EV may be an efficient therapeutic candidate for UC.